DEVELOPING SUPPLEMENTARY MATERIAL FOR VII GRADE OF AVERAGE LEARNERS IN HONOURS CLASS AT SMP NEGERI 2 UBUD - Dewi, Ida Ayu Putu Utami; Nitiasih, Putu Kerti; Suputra, Putu Eka Dambayana (Undiksha Press, 2024)
The objective of this study was to create additional educational resources in English, specifically tailored for students in the 7th grade who have a slower learning pace at the junior high school level. This investigation was conducted at SMP N 2 Ubud. The software incorporates learning activities that are based on problem-based learning (PBL), project-based learning (PjBL), and discovery-based learning (DBL) methodologies. The product was developed using the D&D approach recommended by Richey and Klein (2007). The ADDE procedures encompass the stages of analysis, design, development, and evaluation. The participants in this study consisted of an English teacher and 70 seventh-grade students from SMP N 2 Ubud. The data obtained from the analysis technique is gathered through the means of observation, interviews, questionnaires, and document analysis. The outcome of the analysis technique was followed by the creation of the blueprint for additional material. The plan was utilized in the product development process. The supplemental material was incorporated into the 7th grade course of the Merdeka Curriculum. The evaluation found that the additional material is suitable for the teacher to utilize as educational media for students with slow learning abilities.